Exploring the anti-tumor mechanisms of thiourea-derived CXCR2 antagonists: a computational perspective - Khadija Zaki; Kamal Tabti; Mohamed Ouabane; Hanane Zaki; Abdelouahid Sbai; Chakib Sekkate; Tahar Lakhlifi; Mohammed Bouachrine (Discover Chemistry)
Abstract Cancer stands as one of the most difficult health challenges, posing significant dangers due to its ability to proliferate uncontrollably and spread throughout the body. CXCR2 is a G-protein coupled receptor that has significant interference in tumor development and metastasis. Its overexpression is related to poor prognosis in various cancer types and malignancies, and its inhibition suppresses tumor growth, angiogenesis, and metastasis of several cancers. Its therapeutic target potential directed us to the study of thirty thiourea derivatives with CXCR2 inhibition activity using the 3D quantitative structure–activity relationship method, where an explaining CoMSIA model was derived. The visualization of the model's contour maps highlighted the positive effect of introducing substituents with bulky hydrophobic effects on the ester moiety and hydrophobic effects on the thiourea moiety, using them we designed thirteen new antagonists with enhanced activities. Furthermore, the binding mode investigation of the newly designed molecules, using molecular docking, revealed strong interactions with active site residues and extra hydrogen bonds. Moreover, dynamic simulation confirmed their stability and sustainability resulting in a desirable outcome of limited protein mobility. Moreover, continued refinement of the highly effective compound candidates will establish a critical theoretical foundation for creating and developing new CXCR2 inhibitors.